Developing Insect Pest Management Systems for Hemp in the United States: A Work in Progress. (28th August 2019) - Cranshaw, Whitney; Schreiner, Melissa; Britt, Kadie; Kuhar, Thomas P; McPartland, John; Grant, Jerome
Abstract: Hemp ( Cannabis sativa L.) is now being grown within the United States over a much broader geographic area and for different uses than during its last period of significant production that ended after World War II. Within the past 3 yr, a large number of arthropod species have been documented to feed on hemp in the United States. Among key pest species, corn earworm, Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae), has demonstrated greatest potential for crop injury, being particularly damaging to flower buds. Hemp russet mite, Aculops cannibicola (Farkas), and cannabis aphid, Phorodon cannabis Passerini, are the two species observed most damaging among those that suck plant fluids. Eurasian hemp borer, Grapholita delineana Walker, is widely present east of the Rocky Mountains and appears to have potential to significantly damage both flower buds and developing seeds. Numerous species of caterpillars, grasshoppers, and beetles chew hemp foliage; the severity of these defoliation injuries appears to be minimal, but needs further study. Similarly, numerous seed feeding hemipterans, most notably stink bugs and Lygus bugs, are regularly found in the crop but injury potential remains unclear. Some preliminary efforts have been made to develop integrated pest management strategies for these insects, particularly for corn earworm. Future research can be expected to rapidly resolve many of the data gaps that presently restrict advancing pest management on the crop. However, a major confounding issue involves the use of pesticides on hemp. Federal agencies have not yet provided clear direction on this issue, and regulatory decisions have subsequently devolved to the states.